Du Pont System Analysis of Companies Listed on the Indonesian Stock Exchange for the 2020–2024 Period - Ika Indrawati; Gregorius Nasiansenus Masdjojo (Manunggal Halim Jaya, 2026)
Du Pont System is a financial analysis framework used to evaluate a company's ability to generate profits while optimizing the utilization of equity owned by shareholders. The population in this study includes companies engaged in the pharmaceutical sector and listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The average Net Profit Margin (NPM) of 8.37% indicates that, in general, pharmaceutical companies are still able to generate net profits from their sales activities. In terms of asset utilization efficiency, the average Total Asset Turnover (TATO) value of 0.76 shows that pharmaceutical companies are not yet fully efficient in utilizing their assets to generate sales. The interaction between profitability and asset efficiency is reflected in the average Return on Investment (ROI) value of 8.09%. From a capital structure perspective, the average Equity Multiplier (EM) value of 1.79 indicates that pharmaceutical companies generally use debt-based financing to a significant extent. The average Return on Equity (ROE) value for the pharmaceutical industry of 9.28% shows that, overall, pharmaceutical companies are still able to provide positive returns to shareholders. The results of the Du Pont System analysis based on industry averages show that the performance of the pharmaceutical sector during the 2020-2024 period is fairly stable, but not yet optimal. Future improvements in industry performance need to focus on strategies to increase asset efficiency and strengthen operational profitability, rather than solely through increased leverage. Thus, pharmaceutical companies are expected to be able to generate healthier and more sustainable financial performance growth.